Implementasi Gamifikasi Terapi Perilaku Kognitif Untuk Mahasiswa Pengidap Gejala Depresi Dengan Konsep Finite State Machines - Zaman, Syamsul; Fergina, Anggun; Somantri, Somantri (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2024)
Cognitive behavioral therapy (CBT) is one of the effective therapies for addressing mental health problems, such as anxiety and depression. CBT helps individuals to identify and challenge distorted thoughts. Gamification is the application of game elements in a non-game context. Gamification can be used to increase user engagement and motivation. Finite state machines (FSMs) are mathematical models used to describe the behavior of systems with a finite number of states. FSMs can be used to model game behavior. The purpose of this study is to design and implement a gamified CBT interactive game using the concept of FSMs. This game will help individuals to identify and challenge distorted thoughts. The game will use the concept of FSMs to model the game behavior. FSMs will be used to track user progress, to generate challenges tailored to the user's needs, and to provide feedback to the user. The game will be tested with users to assess its effectiveness.